The Ural Owl, Strix uralensis macroura, in Slovenia - Vrezec, Al; Mihelič, Tomaž (Rivista Italiana di Ornitologia, 2012)
In Slovenia the Ural Owl, Strix uralensis macroura, is on the north-western limit of its distribution with an estimated population size of 400-700 breeding pairs. The densities of territories range between 0.9 to 13.4 territories per 10 km2, and the highest densities are reached in montane forests of the southern Dinaric region. In the forests with dominant deciduous trees, e.g. Fagus sylvatica and Quercus robur, the breeding densities are significantly higher than in the forests with a higher proportion of coniferous trees, e.g. Picea abies. The species does not select specific altitude and throughout Slovenia it occurs between 150 and 1600 m a.s.l. Most natural nests were found in tree holes or semi-holes (56%) and on the tree stumps (20%). Breeding begins between 15 March to 21 June with median clutch sizes of 3.0 eggs per nest. In the brood there are 2 young and 1.5 young are fledged in median. At present 75% of nests produce at least one young. Voles and Mice are the most frequent prey in the diet, but the Fat Dormouse, Glis glis, seems to have very important role in the post-breeding period. As a top predator, the Ural Owl influences also the distribution of other owl species in the guild through direct predation or competitive exclusion. However, it could have also a positive indirect effect on smaller species, e.g. Tengmalm’s Owl, Aegolius funereus, which are tolerated within Ural Owl territories, and are able to extend their distribution due to exclusion from certain areas of the Tawny Owl, Strix aluco, by the Ural Owl.